Trade liberalisation and human rights protection under the SADC - Jjuuko, Frederick W. (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Prof Fredrick Jjuuko, Faculty of Law, Makerere University, Kampala, Uganda.